1980
DOI: 10.1111/j.1432-1033.1980.tb04517.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Profilactin and Profilin from Calf Thymus and Brain

Abstract: Profilactin and profilin have been purified from calf thymus and calf brain. Thymus profilactin could be crystallized with a similar technique as described earlier for the spleen protein. Preparations of profilactin from the three calf tissues spleen, thymus and brain contain a mixture of β actin and γ actin. The ratio β/γ differs between the tissues, but is constant throughout the purification steps. The properties of profilin isolated from three sources (spleen, thymus and brain) indicate that it is a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Profilin was first isolated from calf spleen (Carlsson et al, 1977) and subsequently found in a variety of other vertebrate tissues (Blikstad et al, 1980;Fattoum et al, 1980;Ohshima et al, 1989). A similar protein was isolated from the invertebrates Acanthamoeba castellana (Ampe et al, 1985;Kaiser et al, 1986;Ampe et al, 1988), P. polycephalum (Osaki et al, 1983;Osaki and Hatano, 1984), and Thyone briareus (Tilney et al, 1983).…”
mentioning
confidence: 97%
“…Profilin was first isolated from calf spleen (Carlsson et al, 1977) and subsequently found in a variety of other vertebrate tissues (Blikstad et al, 1980;Fattoum et al, 1980;Ohshima et al, 1989). A similar protein was isolated from the invertebrates Acanthamoeba castellana (Ampe et al, 1985;Kaiser et al, 1986;Ampe et al, 1988), P. polycephalum (Osaki et al, 1983;Osaki and Hatano, 1984), and Thyone briareus (Tilney et al, 1983).…”
mentioning
confidence: 97%
“…With 30 pM platelet profdin there was no inhibition in 2 mM MgClz. However 34/zM spleen, brain, or thymus profdin all inhibited the steady-state viscosity of muscle actin >90% in 2 mM CaCI2 (2). There were no experiments to test whether the buffer composition (especially the divalent cation) might explain these differences.…”
mentioning
confidence: 99%
“…It is difficult to compare the four different published studies, because there is no uniformity in the buffer conditions or the concentration or type of actin. In five published experiments using 14 to 18 tzM muscle actin in phosphate buffer with 2 mM MgCI2 or CaC12, 8 to 12 btM profilin from brain, spleen, thymus (2), or platelets (9) inhibited the steady-state viscosity <20%. With 30 pM platelet profdin there was no inhibition in 2 mM MgClz.…”
mentioning
confidence: 99%
“…Profilin is a 12-15 kDa protein that initially was isolated from bovine spleen [l] and subsequently found to be expressed in several mammalian tissues such as thymus, brain, platelets [2][3][4], thyroid gland [5], macrophages [6], liver, spleen, uterus, heart, lung and kidney [7]. Human profilin shows 95% identity to bovine profilin and the amino acid exchanges are mainly conservative [7].…”
Section: Introductionmentioning
confidence: 99%